Trialling monitoring methods for feral cats, ferrets and rodents in the Whangamarino wetland. Issue 3 (3rd July 2018) - Gillies, Craig; Brady, Matthew
ABSTRACT: The Whangamarino wetland in New Zealand is one of three nationally important sites managed under the Department of Conservation's Arawai Kākāriki programme. Reducing populations of introduced predatory mammals to levels that will allow the recovery of threatened wetland birds is a key objective of the programme. However, existing monitoring techniques designed for measuring small pest mammal abundances in other environments may not be appropriate for the Whangamarino wetland. Between 2010 and 2014 we tested simple camera trap indices of ferret ( Mustela furo ) and feral cat ( Felis catus ) relative abundances and PCR WaxTag bite mark indices of rat (Norway rat Rattus norvegicus and ship rat R. rattus ) and house mice ( Mus musculus ) relative abundances by comparing them to live-trap indices of pest abundances in the Whangamarino wetland. We found that there were strong positive correlations between the camera trap indices and the associated live-trap indices of ferret abundances. There were modest, but significant positive correlations between camera trap indices and the associated live-trap indices of feral cat abundances. We also found that both 3-night and 7-night PCR WaxTag bite mark indices of rat or mouse abundances correlated strongly and positively with associated live-trap indices. We concluded that camera traps can be used to monitor ferret and feral cat abundances and PCR WaxTags can be used to monitor rodent abundances in the Whangamarino wetland and other environments.